A Note on Estimating the Importance of Interactions among Economic Entities - Emilian Dobrescu (Amfiteatru Economic)
In a maximally simplified scheme, the economy is an immense network of interacting entities (individuals, households, firms, institutions, regions, countries, international unions), reducible in the last instance to an, again, huge graph of transactions (in the largest sense). Well known couples as seller-buyer, lender-borrower, exporter-importer, tax payer-fiscal authority etc. personify this double-entry framework. The national accounts, input-output tables, general equilibrium models are several modalities to configure and study this complicated system in a coherent framework. A theoretical and applicative challenge continues to be “how to evaluate quantitatively the relative importance of a given concrete transaction from the perspective of the entire economy (the totality of transactions)”. The present note tries to answer to such a problem starting from the positions detained in economy by the involved in transactions entities. As an applicative example, there are used the Romanian yearly input-output tables for 1989-2016.